Severe Paediatric Asthma Collaborative in Europe (SPACE): protocol for a European registry. Issue 2 (June 2018) - Liu, Norrice M.; van Aalderen, Wim; Carlsen, Karin C.L.; Coleman, Courtney; Chalmers, James D.; Cunningham, Steve; Fernandes, Ricardo M.; Fleming, Louise J.; Gappa, Monika; Karadag, Bülent; Midulla, Fabio; Pijnenburg, Marielle W.H.; et al.
The development of new asthma biologics and receptor blockers for the treatment of paediatric severe asthma raises challenges. It is unclear whether there are sufficient children in Europe to recruit into randomised placebo-controlled trials to establish efficacy and safety in this age group. In February 2016, the European Respiratory Society funded a clinical research collaboration entitled "Severe Paediatric Asthma Collaborative in Europe" (SPACE). We now report the SPACE protocol for a prospective pan-European observational study of paediatric severe asthma. Inclusion criteria are: 1) age 6–17 years, 2) severe asthma managed at a specialised centre for ≥6 months, 3)clinical and spirometry evidence of asthma, and 4) reaching a pre-defined treatment threshold. The exclusion criterion is the presence of conditions which mimic asthma symptoms. Eligible children will be prospectively recruited into a registry, recording demographics, comorbidities, quality of life, family history, neonatal history, smoking history, asthma background, investigations, and treatment. Follow-up will provide longitudinal data on asthma control and treatment changes. The SPACE registry, by identifying well-phenotyped children eligible for clinical trials, and the amount of overlap in eligibility criteria, will inform the design of European trials in paediatric severe asthma, and facilitate observational research where data from single centres are limited. An ERS funded clinical research collaboration has developed a protocol for a paediatric severe asthma study to support asthma biologics trials http://ow.ly/YQkW30j32xJ